2018
DOI: 10.1016/s2214-109x(18)30389-9
|View full text |Cite
|
Sign up to set email alerts
|

Equity in antenatal care quality: an analysis of 91 national household surveys

Abstract: SummaryBackgroundEmerging data show that many low-income and middle-income country (LMIC) health systems struggle to consistently provide good-quality care. Although monitoring of inequalities in access to health services has been the focus of major international efforts, inequalities in health-care quality have not been systematically examined.MethodsUsing the most recent (2007–16) Demographic and Health Surveys and Multiple Indicator Cluster Surveys in 91 LMICs, we described antenatal care quality based on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
183
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(204 citation statements)
references
References 36 publications
13
183
1
7
Order By: Relevance
“…Major ethnic, cultural and economic differences exist across regions in Kenya and the region dummies may capture some of these unmeasured factors. For example, others have found that women in lower wealth quintiles and those living in multidimensionally poor areas tend to receive lower quality maternity care . Kenya has had a long history of decentralisation dating back to the early 1980s, and differences in policies and resource allocation between regions may explain the variation in quality of care .…”
Section: Discussionmentioning
confidence: 99%
“…Major ethnic, cultural and economic differences exist across regions in Kenya and the region dummies may capture some of these unmeasured factors. For example, others have found that women in lower wealth quintiles and those living in multidimensionally poor areas tend to receive lower quality maternity care . Kenya has had a long history of decentralisation dating back to the early 1980s, and differences in policies and resource allocation between regions may explain the variation in quality of care .…”
Section: Discussionmentioning
confidence: 99%
“…One reason may be that they have the fewest choices in the type of provider they can access, because they lack the resources needed to bypass local facilities to seek better-quality care elsewhere. 6,35,36…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Addressing inequities in access to and quality of health care is a priority now more than ever, as the poorest members of communities continue to bear the largest burden of ill health and consistently receive lower-quality care. 5,6 Recognizing this situation, health programmers in low-and middle-income countries have, over the past decade, aimed to implement strategies that favour the poorest members of communities and promote community linkages within primary health care. [7][8][9][10] Certain interventions, such as training community members to make health promotion visits to families, have improved the practice of healthy behaviours in communities and increased care-seeking in health facilities.…”
mentioning
confidence: 99%
“…Previous studies examined the utilization of maternal healthcare through combinations of factors including inequity, wealth, education, region, ethnicity, religion, occupation, and migration status. (Arsenault et al, 2018;Braveman, 2005;Harper et al, 2008;Zere et al, 2013). Secondly, it used a single indicator (skilled birth attendant) of quality antenatal care whereas previous studies used a variety of measures, such as the number of antenatal care visits, institutional delivery of a child, and the increase of tetanus injections (Gebre, Worku & Bukola, 2018;Hajizadeh et al, 2014;Majrooh et al, 2014;Mwase et al, 2018;Nair & Panda, 2011).…”
Section: Resultsmentioning
confidence: 99%